PREFERENSI DAN PENDUGAAN PRODUKTIVITAS PAKAN ALAMI POPULASI GAJAH SUMATERA (Elephas maximus sumatranus Temmick, 1847) DI HUTAN PRODUKSI KHUSUS (HPKh) PUSAT LATIHAN GAJAH (PLG) SEBELAT, BENGKULU UTARA - Yanto Santosa; Supartono .; Machmud Thohari (Department of Forest Resources Conservation and Ecotourism - IPB University, 2011)
The isolation of habitat, shrinking of natural habitat and diminishing of habitat quality have increased conflicts between man and elephant to utilize space and abundance of food. This research was carried out from April to June 2007 in Seblat Training Centre for Elephants. The objectives of this research were to recognize the potential of food plants for the elephants, the productivity of food plants, types and parts of food plants favoured by the elephants, and preferential of specific food plants and feeding behaviour. The analysis was conducted by means of vegetation analysis, through cutting and pruning parts of feeding plants, studying them and running statistical procedures to acquire conclusions about the food plant species. The analysis was followed by observing the feeding behaviour of the elephants on foot. Ground plant species which were potential as elephants’ feed comprised of 36 species, 29 spesies at seedling level, 26 species at sapling level, 24 species at pole level and 29 species at tree level. The highest productivity for sapling and pole levels are Leea indica and for seedling level is Gigantochloa cf. atroviolacea. The feeding plants of elephants comprises of 245 species from which 11 parts of the plants preferred by the elephants. Gigantochloa cf. atroviolacea and Stachyphrynium sp were the most favored plant species, indicated by the highest preferential index. The feeding behaviour of elephants could be categoried into 8 categories. Keywords: Sumatran elephant, Seblat Training Center of Elephants, preferential, productivity.